Numerical modelling of the strengthening process of steel-concrete composite beams = Numeryczne modelowanie procesu wzmacniania stalowo-betonowych belek zespolonych - Szewczyk, Piotr; Szumigała, Maciej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the numerical modelling of strengthening a steel-concrete composite beam. The main assumption is that the strengthening is not the effect of the state of a failure of a structure, but it resulted from the need to increase the load-bearing capacity and stiffness of the structure (for example: due to a change in the use of the object).
Keywords: metoda elementów skończonych; belki zespolone; wzmacnianie; analiza nieliniowa; Finite Element Method (FEM); composite beams; strengthening; non-linear analysis